Food security, agricultural production, and market trends in 1998: the full story - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
FAO's report for 1998 focuses on food supply for large towns and the complex interaction of factors affecting the integration of agriculture and fisheries. A special chapter is devoted to nonagricultural rural earnings and employment, which provide...